PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT ELNUSA Tbk - Sebastian Arthur Hasian Hukom (2022)
This research is a quantitative study that aims to determine whether there is an influence of leadership, organizational culture, and job satisfaction on the work productivity of employees of PT Elnusa Tbk. This study uses 100 respondents. The hypothesis in this study is to determine the effect both partially and simultaneously of the X and Y variables, so the tests used are the coefficient of determination test, f test and t test. Furthermore, the research results obtained are: (1) leadership has a positive and significant influence on employee work productivity, (2) organizational culture has a positive and significant influence on employee work productivity, (3) job satisfaction has a positive and significant effect with employee work productivity, (4) leadership, organizational culture, and job satisfaction simultaneously have a significant effect on the work productivity of employees of PT Elnusa Tbk..